Updating the classification and content of analytical tools for construction preparation on the basis of digitalization - Malykhin, M.O. (Ways to Improve Construction Efficiency, 2023)
The topic of classifying and updating the content of analytical tools for construction preparation on the basis of the digital economy is becoming increasingly relevant in the context of rapid technological evolution. The digital economy has led to a positive transformation of traditional project management and analysis methods, enabling construction companies to apply modern analytical tools that optimize processes and increase efficiency at all stages of construction preparation. The process of preparing a construction project requires the use of tools that can take into account multifactorial variables and analyze complex relationships between different elements of the project. The use of digital technologies allows not only to accurately model various project development scenarios, but also to create effective forecasting models. The updated classification of analytical tools in the digital economy is based on the need to recognize new types of data, changes in the ways they are processed, and the use of analytical platforms such as BIM (Building Information Modeling), CAD (Computer Aided Design), artificial intelligence, and machine learning. Background. The digital economy is changing the paradigm of construction project preparation, offering construction companies the opportunity to use comprehensive tools to automate routine processes, analyze large amounts of data, and optimize decision-making. Analytical tools are now aimed at closer integration with project management information systems, which allows for more effective coordination of various stages of construction work and reduces the risks associated with the execution of work. Innovative technologies such as blockchain and the Internet of Things (IoT) also create new opportunities for managing the construction preparation process and expand the horizons of the analytical platform. There are three main categories of analytical tools that have been updated in accordance with the requirements of the digital economy: data collection tools, data processing tools, and forecasting tools. Within these categories, automated methods of data analysis and visualization are being actively implemented, which can significantly reduce the time required for preparatory work and increase the accuracy of decision-making. Analytical tools also include resource optimization tools that take into account changes in the economic environment in real time and ensure the rational use of materials, labor resources and funds.